PENGARUH MENONTON ACARA TELEVISI TERHADAP PERKEMBANGAN BAHASA DAN SOSIAL EMOSIONAL PADA ANAK USIA 3-5 TAHUN - Maduratna, Enggal Sari (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2085)
Language is the result of word-processing has expanded, while social emotionalmaturity is the achievement of children in their social relations . From the preliminary studyof 10 children acquired 6 children (60%) have not been able to perform the duties of languagedevelopment , such as has not been able to repeat the simple story and has not been able tocommunicate well . While 7 children (70%) do not have the confidence and self-sufficiencyas well as interaction with peers are lacking. This study was to analyze the effect of watchingtelevision on the social and emotional development of language in children aged 3 -5 yearsThe design of this study is Analytical Correlation with Cross Sectional approach .Independent variable is Watching television shows and the dependent variable is thedevelopment of language and social emotional. The population is 26 children withProportional Stratified Random Sampling technique obtained a sample of 20 children. Thecollection tool is using questionnaires and KPSP. Univariate and bivariate analysis are usingfrequency distribution and statistical test Spearman Rank.Spearman Rank test results, showing that there is influence of watching television forlanguage development of children aged 3-5 (? value = 0.001), there is influence of watchingtelevision for social emotional development of children aged 4-6 years (? value = 0.001) andalmost half of children aged 3-5 watch television in weight category about of 45% .The results of this study can be used as inputs for parents that television viewingpatterns can affect a child's development. With the result that parental supervision whilewatching television is needed to minimize the negative effects that may occur by limiting thetime children watch television ? 2 hours per day.